Muscle mass loss is associated with physical dysfunction in patients with early rheumatoid arthritis - Pan, Jie; Zou, Yao-Wei; Zhu, Ying-Ying; Lin, Jian-Zi; Wu, Tao; Yang, Ze-Hong; Zhang, Xue-Pei; Zhang, Qian; Zheng, Hu-Wei; He, Xiao-Ling; Cheng, Wan-Mei; Ma, Jian-Da; et al. (Frontiers in Nutrition, 2022)
Background: Muscle mass loss is common in long-standing rheumatoid arthritis (RA). Our aim was to explore its prevalence and effects on RA disease characteristics in patients with early RA. Methods: This cross-sectional study was carried out based on a Chinese RA cohort and control subjects. Body composition (BC) was assessed using bioelectric impedance analysis. Myopenia was defined by appendicular skeletal muscle mass index ≤ 7.0 kg/m2 in men and ≤ 5.7 kg/m2 in women. Physical dysfunction was defined as health assessment questionnaire disability index > 1. Propensity score matching was performed to balance age and gender difference among patients with early RA (disease duration ≤ 12 months), established RA and controls (in 1:3:3 matching). Results: There were 2017 controls and 1008 RA patients recruited. Among RA patients, there were 190 (18.8%) patients with early RA with median disease duration 7(4,11) months. Matched patients with early RA (n=160) showed a higher prevalence of myopenia than matched controls (41.3% vs. 15.8%, P < 0.0167), but no difference with matched patients with established RA (41.3% vs. 50.4%, P > 0.0167). Compared with patients with established RA, patients with early RA exhibited higher disease activity scores [Disease Activity Score in 28 joints with four variables including C-reactive protein (DAS28-CRP): median 4.76 vs. 3.93, P < 0.001] and higher prevalence of physical dysfunction (26.3% vs. 19.4%, P = 0.035). In patients with early RA, patients with myopenia showed higher prevalence of physical dysfunction than those without myopenia (41.3% vs. 15.5%, P < 0.001), among which walking and common daily activities were the most involved subdimensions. Multivariate logistic regression analysis showed that DAS28-CRP was positively associated with myopenia [adjusted odds ratio (AOR) 1.558, 95% CI (1.138-2.132)], and myopenia [AOR 2.983, 95% CI (1.192-7.465)] was independently associated with physical dysfunction in patients with early RA. Conclusions: Our data indicate the importance of early detection of muscle involvement in early stage of RA and imply the significance of early aggressive control of disease activity for prevention from myopenia and physical dysfunction in patients with early RA. Our study provides a new perspective for RA management.